O corpo da mulher enquanto resistência: sobre a insurgência por meio de um direito novo - Gabriella De Morais (2020)
Based on the critique of sovereign law as a biopolitical instrument, we sought to demonstrate that law, as well as legal discourse, as manifestations of power legitimize social norms that keep women sewn into subjectivities limited to the functions of care, affection, sensuality and motherhood; what makes these bodies are directed to serve the other. So that when this body rises and denies these subjectivities, it becomes abject, in the sense proposed by Julia Kristeva and Judith Butler. The condition of abjection makes the body that was read as a woman become unreadable. And when the body becomes unreadable it can be abandoned to death. At this point, the criticism of the law is presented through its own structure: laws, sentences and the performance of those who may be the interpreters of the truth. Such an analysis reveals that the law, as the locus of justice, fulfills the desires of those who have the power of discourse: the bearers of the phallus. This situation leads us to the proposal to break with the sovereign right using practices – in and of the body – that would be contrary to governmentality. These practices can be read as acts of counter-conduct and critical attitude, being necessary for the creation of what Foucault called a new law.